Evolution of Mentoring Relationships Involving Young Male Offenders Transitioning from a Juvenile Justice Centre to the Community. (August 2017) - Hanham, José; Tracey, Danielle
This qualitative longitudinal study focused on adolescent males who were being formally mentored during their transition from a juvenile justice centre to the community. Pre-release, the young men feared being exposed to negative peer influences and uncertainty about the future. In response to this anxiety, the young men valued the mentor as a guide, confidant and "watchdog". Post-release, the concerns of the young men turned to a sense of disconnection, institutionalisation and difficulties securing employment. Here, the young men required their mentors to be reliable, build confidence and assist with educational and occupational opportunities. The findings both inform our theoretical understanding of mentoring and provide direction for supporting young offenders in the transition back into the community.